Influences of 1,2-dichlorobenzene on bacterial community structure in wetland soil - Huixing, Liang; Aihui, Chen; Zhaoxia, Li; Muhammad Aqeel Ashraf,; Cheng, Ding (Universiti Kebangsaan Malaysia, 2016)
In order to explore the response of the soil microbial community to 1,2-dichlorobenzene exposure in Wetland soil, a short-term (7 weeks) mesocosm study was conducted at four 1,2-dichlorobenzene concentrations of (100, 400 and 800) μg g -1. Dry soil, sterile and unsterile controls were also compared. The results obtained showed a significant effect of 1,2-dichlorobenzene on the development of bacterial populations in soils contaminated with different concentrations of 1,2-dichlorobenzene at the early time after application. In general, however, the number of populations of the same soil sample treated with the same concentration of 1,2-dichlorobenzene differed significantly with the increasing incubation time within the early 5 weeks. The scale of differences in banding patterns-showed that the microbial community structures of 1,2-dichlorobenzene-treated and non-1,2-dichlorobenzene-treated soils were not significantly different after 7 weeks of incubation. DNA in application-responsive bands from the 1,2-dichlorobenzene treatments was recovered and amplified using the universal primers. PCR products were recovered and cloned into pGEM-T Easy (Promega) and two clones were obtained. The two clones were sequenced using the automated Model 3730 DNA sequencing system. The two cloned sequences had very high similarities to an uncultured bacterium reported previously in the database of NCBI.